A comprehensive dynamic model for downdraft gasifier using heat and mass transport coupled with reaction kinetics. (1st December 2016) - Patra, Tapas Kumar; Nimisha, K.R.; Sheth, Pratik N.
Abstract: A dynamic multiphase model combining mass and energy transport with kinetics for the gasification of wood in a downdraft gasifier is developed. The developed model takes into account the mass and energy balance of both solid and gas species. It also includes the reaction kinetics of various phenomena i.e. drying, pyrolysis, combustion and reduction occurring inside the gasifier. The global kinetics of pyrolysis, combustion kinetics of gaseous and solid species, homogenous and heterogeneous reduction kinetics and diffusion controlled moisture evaporation are incorporated in the model. The developed model is simulated to predict various variables such as biomass consumption rate, producer flow rate and its composition throughout the gasifier at various locations at different time. The model is validated with the experimental data reported in our earlier study. The simulation results are found to be well in agreement with the experimental data. The dynamic behavior of downdraft gasifier is studied by analyzing the axial profiles of temperature, concentration and density at different time. Highlights: A multiphase dynamic model is developed & simulated for downdraft biomass gasifier. The model is 1 D and combines transport and kinetic process of biomass gasification. The reaction kinetics of all the chemical processes are incorporated in the model. The predictions are validated with various parameters of different equivalence ratio. Dynamic profiles of temperature, velocity, composition of outlet gas are reported.